Genetic Differentiation of Eastern Honey Bee (Apis cerana) Populations Across Qinghai-Tibet Plateau-Valley Landforms - Yu, Yinglong; Zhou, Shujing; Zhu, Xiangjie; Xu, Xinjian; Wang, Wenfeng; Zha, Luo; Wang, Ping; Wang, Jianwen; Lai, Kang; Wang, Shunhai; Hao, Lunan; Zhou, Bingfeng (Frontiers in Genetics, 2019)
Many species of high-altitude plateaus tend to be narrowly distributed along river valleys at lower elevations due to a limitation of suitable habitats. The eastern honeybee (Apis cerana) is such a species and this study explored the effects of long and narrow geographic distributions on honeybee populations. Genetic differentiation and diversity were assessed across populations of the southeastern Qinghai-Tibet Plateau. A total of 492 honeybee samples from eight sampling sites in four valleys were analyzed for the genetic differentiation and diversity of 31 microsatellite loci and mitochondrial tRNAleu–COII fragments. The following results were obtained: (1) Microsatellite genetic differentiation coefficients (FST) ranged from 0.06 to 0.16, and mitochondrial FST estimates ranged from 0.18 to 0.70 for different sampling sites in the same valley, indicating genetic differentiation. (2) Honeybees in adjacent valleys were also genetically differentiated. The FST of microsatellites and mitochondria were 0.04–0.29 and 0.06–0.76, respectively. (3) Likely a result of small population sizes, the observed genetic diversity was low. The observed impedance of honeybee gene flow among valleys increased both genetic differentiation and population numbers in the Qinghai-Tibet Plateau. This study contributes significantly to the current understanding of the mechanism underlying population genetic differentiation and highlights the potential effects of utilizing genetic resources that are subject to the ecological conditions of the long and narrow geographic distributions of plateau-valley landforms.